Efektivitas Terapi Dzikir dan Shalat dalam Menurunkan Tingkat Stres pada Lansia - Ningsih, Ike Utia; Pakam Juanda (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to explore the effectiveness of dhikr and prayer therapy in reducing stress levels in the elderly. Stress is one of the psychological disorders often experienced by the elderly due to physical, social and emotional changes that occur with age. In the Islamic context, worship such as dhikr and prayer not only has a spiritual dimension, but can also function as a form of psychological therapy that calms the soul. This research uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation of several elderly people who routinely practice dhikr and prayer in the environment of houses of worship and elderly communities. The results showed that the consistent practice of dhikr and prayer can provide inner peace, reduce stress symptoms, and increase the meaning of life in the elderly. This spiritual therapy proved effective as a form of non-medical intervention that is easily accessible and in accordance with the religious values of Muslim elderly. The implications of this study are expected to be a reference in a holistic approach to elderly mental health based on Islamic values.